Meningkatkan Kemampuan Daya Cipta Anak Melalui Metode Bermain Peran di Kelompok B TK Teratai Sunju - Ivana, Nur (Bungamputi, 2014)
ABSTRACT The background of this research is the existence of the problem of create ability of child which is not yet maximal caused by less applying teacher of skill of teaching base. APE less available and also the tools and infranstructure are not supporting. Beside that the ability of child also become one of the factor cause of ability of energ create child less maximal. Hence conducted by repair of study process with aim to increase the result of learning, one of them is the ability of energy create child. Repair action used is method playing at proven role can improve the ability of energy create child. Device research of this class action which started from reflection planning of execution and observation. Its subyect is group B of 25 children which consist of 13 daughters and 12 boys. Technique collecting data use giving observation and documentation, hereinafter analysed with presentation technique. Result of research prove that at cycle one ability of energy create mean child categorize very good and goodness mount to become 45 %. At the second cycle mounting to become 80 %. So that can be concluded that method playing at role can improve ability of energy create children in group B of Teratai Kindergarthen Sunju. Although there arestifi not yet succeeded to mount its ability 20 %. Â  Keyword: the ability of create, method of playing at role